A practical method for predicting shear deformation of reinforced concrete beams. (1st March 2020) - Huang, Zheng; Tu, Yongming; Meng, Shaoping; Ohlsson, Ulf; Täljsten, Björn; Elfgren, Lennart
Highlights: A piecewise model was proposed to characterize the shear force-mean shear strain curve for the sections of RC beams. A practical method for predicting shear deformation of RC beams was developed based on FE analysis. The proposed method was validated against a database comprised of 76 test beams. Abstract: This paper presents a practical method for predicting the deflections, including both the flexure and shear contributions, of reinforced concrete (RC) beams. The shear force-shear strain ( V - γ ) curve of a section in the shear span of RC beams is represented by a piecewise model and the tangent shear stiffness after shear cracking, Kt, cr, is assumed to be constant. A 2D finite element model, which has been validated for predicting shear deformation of RC beams, was used to identify factors that may affect the shear reduction factor (the ratio of Kt, cr to the elastic shear stiffness) and establish methodology for predicting the V - γ curve. Two types of methods, integration-form and closed-form, for predicting the total deflection were developed, in which the flexure-induced deflection (FD) was predicted using the Bischoff model while the shear-induced deflection (SD) was predicted using the method proposed in this paper. Comparison of the predictions with experimental results confirms that the Bischoff model provides reliable predictions of FDs of RC beams with and without shrinkage. It also shows that the proposed method can provide accurate predictions for SD after shear cracking, provided the effect of shrinkage on the shear cracking load is adequately quantified.